Numerical modelling of residual stress redistribution induced by TIG-dressing: TIG-dressing numerical modelling (Fracture and Structural Integrity, 2018)
TIG-dressing is a technique used to improve the fatigue strength of welded joints by a remelting of the weld toe region that promotes both a smoother transition between the plate and the weld crown and a residual stress redistribution. These effects are very hard to be quantified by numerical simulation since a highly coupled thermo-fluid-mechanical analysis is required. However, if the final weld toe geometry is supposed to be known or a-posteriori measured, a simplified numerical method can be used to simulate the residual tress redistribution that uses the activation-deactivation function of elements. This technique is applied to a real steel weldment and results, in terms of phases proportions and residual stress redistribution, were found in good agreement both with data coming from metallurgical analysis and the improved fatigue strength observed on welded joints after the TIG-dressing operation.
Keywords: Numerical modelling; Welding; TIG-dressing; Residual stress; Microstructure; Phase transformation